Well I can give you one way
you can right an equivalent expression by taking to expressions that equal the same like this 1+4=3+2
I hope that helps
hes right above what he said
An example would be:
3x^2 + 6
3(x^2 + 2) .
The second way is found by dividing the first one by 3).
1. 1 – n = 0.
Other same examples, John bought 25 apples while Julia bought only 15 from the market. If Niccole bought twice as much as Julia’s, how many was Niccole’s apples?
1. You state the problem by the sequence of the said problem and understanding the possible structure.
2. Solution will be Julia = 15 apples Niccole = 2Julia
Hence, 2Julia = 2(15) = 30 apples.
answer: it is d